2018
DOI: 10.1002/cpp.2345
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of metacognitive interventions for mental disorders in adults—A systematic review and meta‐analysis (METACOG)

Abstract: We evaluated the effectiveness and acceptability of metacognitive interventions for mental disorders. We searched electronic databases and included randomized and nonrandomized controlled trials comparing metacognitive interventions with other treatments in adults with mental disorders. Primary effectiveness and acceptability outcomes were symptom severity and dropout, respectively. We performed random‐effects meta‐analyses. We identified Metacognitive Training (MCTrain), Metacognitive Therapy (MCTherap), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 72 publications
1
41
1
1
Order By: Relevance
“…Talking therapies designed to improve metacognition (metacognitive therapy and metacognitive training) across a range of mental disorders have been developed and tested in small clinical trials. A systematic review 17 found 19 controlled studies in schizophrenia, of which 15 were randomised. The results approached significance when compared with standard or other psychological treatments, with a pooled standard mean difference in positive symptoms scores estimated to be −0.31 (95% CIs −0.50 to −0.12).…”
Section: Metacognitive Therapiesmentioning
confidence: 99%
“…Talking therapies designed to improve metacognition (metacognitive therapy and metacognitive training) across a range of mental disorders have been developed and tested in small clinical trials. A systematic review 17 found 19 controlled studies in schizophrenia, of which 15 were randomised. The results approached significance when compared with standard or other psychological treatments, with a pooled standard mean difference in positive symptoms scores estimated to be −0.31 (95% CIs −0.50 to −0.12).…”
Section: Metacognitive Therapiesmentioning
confidence: 99%
“…This is the first large RCT testing the long-term effects of group MCT on clinical and cognitive insight in addition to several relevant clinical outcomes in a representative sample of patients with schizophrenia spectrum disorders. Although MCT has been consistently demonstrated to improve positive symptoms [14][15][16][17][18], the benefits of MCT on insight are yet to be established [3], which is of major clinical relevance given the association of insight with outcomes in schizophrenia and related disorders [2]. This is supported further by three previous trials which revealed other non-MCT metacognitively oriented treatments to have a positive impact on insight [20][21][22].…”
Section: Relevance and Impactmentioning
confidence: 94%
“…Under these assumptions, for reaching a sufficient statistical power of β = 80% at the end of the study, we will need n = 63 subjects in each arm, that is, a total sample size of N = 126 patients, who will be analysed at the end of the study on an intention-to-treat (ITT) basis. Attrition rates in previous RCTs investigating MCT effects on symptoms were low (approximately 10%) [18]. However, since we will follow-up patients over a more prolonged period (1 year) we have conservatively assumed a much higher drop-out rate of 50%.…”
Section: Power Calculations and Estimation Of Sample Sizementioning
confidence: 99%
See 2 more Smart Citations